THE EFFECT OF RETURN ON ASSETS AND CURRENT RATIO ON FINANCIAL DISTRESS USING THE SPRINGATE METHOD IN TECHNOLOGY COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2019-2021 - Viona Lavidya; Zulkifli Zulkifli (RTTM, 2023)
This study aims to influence Return on Assets (ROA) and Current Ratio (CR) on Financial Distress in technology companies listed on the Indonesia Stock Exchange. The population of this study amounted to twenty six companies. The sampling technique using purposive sampling method obtained six companies. The research results prove that ROA has no significant effect on Financial Distress. Meanwhile, CR has a positive and significant effect on Financial Distress in technology companies listed on the Indonesia Stock Exchange.